Optical element, optical instrument, imaging apparatus, method for manufacturing optical element, light-shielding film, and light-shielding paint
The optical element with a light shielding film and a ramped chamfered portion addresses stress issues in cemented lenses by preventing film accumulation and enhancing thermal shock resistance and cleaning resistance.
Patent Information
- Application Number
- JP2024024594
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2024-02-21
- Publication Date
- 2025-04-03
AI Technical Summary
Cemented lenses with chamfered portions face stress issues due to light shielding films accumulating in grooves, leading to peeling, cracking, and reduced thermal shock resistance.
An optical element with a light shielding film containing resin and inorganic particles, applied to the end surface of a cemented lens with a chamfered portion, featuring a resin ratio of 87 vol% or more and 95 vol% or less, and a ramp on the bonding surface side to prevent film accumulation.
The solution prevents cracking of the lens under harsh thermal shocks, enhances cleaning resistance, and maintains high internal reflection prevention performance.
Smart Images

Figure 2025048701000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical element, an optical instrument and an imaging device having the optical element, and a method for manufacturing the optical element. The present invention further relates to a light-shielding film and a light-shielding paint provided on the surface of the optical element. [Background technology]
[0002] Optical elements used in optical instruments are provided with a black light-shielding film in the outer region of the effective beam diameter as necessary to reduce stray light. The light-shielding film is a film formed on the outer region of glass or plastic, which is a component of an optical element. Here, the glass or plastic may be a lens or a prism. It may also be other optical glass or optical prism.
[0003] Patent Document 1 discloses an optical element that includes a resin component containing a pigment for adjusting the refractive index in relation to a cemented lens having a chamfered portion, and Patent Document 2 discloses a black light-shielding film and an optical element that include a resin, a coloring material, and inorganic particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-024331 A [Patent Document 2] JP 2013-100456 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the cemented lens having the chamfered portion described in the film of Patent Document 1, the light-shielding film accumulates in the groove due to the presence of the chamfered portion. The light-shielding film of Patent Document 1 does not disclose the resin content, and when a large thermal shock is applied, stress is generated in the lens, which may cause the light-shielding film to peel off or the lens to crack or break.
[0006] Patent Document 2 describes an example in which the light-shielding film contains a large amount of resin, but does not mention the concept of cemented lenses, nor does it mention chamfered edges. Without chamfered edges, the lens may chip. In addition, it does not consider the case where the light-shielding film accumulates in the chamfered edges, causing stress.
[0007] The present invention has been made in view of the above-mentioned background art, and provides an optical element having a light-shielding film formed on an end face of a cemented lens having a chamfered portion which is susceptible to stress, which prevents the lens from cracking even when subjected to severe thermal shock, has high washability, and has high anti-internal reflection performance, as well as an optical apparatus and an imaging device having the same, a light-shielding film formed on the optical element, and a light-shielding paint. [Means for solving the problem]
[0008] The present invention is an optical element having a first optical element, a second optical element, a third optical element bonding the first optical element and the second optical element, and a light-shielding film containing a resin and inorganic particles provided in contact with end faces of the first optical element, the second optical element, and the third optical element, wherein the first optical element and / or the second optical element have a chamfered portion on the bonding surface side, and at least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, and the resin ratio of the light-shielding film is 87 vol% or more and 95 vol% or less.
[0009] The present invention also provides an optical device having a housing and the above-described optical element disposed inside the housing.
[0010] The present invention also provides an imaging device including a housing, an optical system including the optical element described above arranged inside the housing, and an imaging element that receives light incident via the optical system.
[0011] The present invention also provides a method for manufacturing an optical element, comprising the steps of: bonding a first optical element and a second optical element with an adhesive that is a precursor of a third optical element; and applying a light-shielding paint to end faces of the first optical element, the second optical element, and the third optical element, and curing the paint to form a light-shielding film, the light-shielding film containing a resin and inorganic particles, the first optical element and / or the second optical element having a chamfered portion on the bonding surface side, and at least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, and the method is characterized in that in the step of forming the light-shielding film, the light-shielding paint is cured so that the resin ratio of the light-shielding film is 87 vol% or more and 95 vol% or less.
[0012] The present invention also relates to a light-shielding film provided in contact with end faces of a first optical element, a second optical element, and a third optical element that joins the first optical element and the second optical element, the light-shielding film comprising a resin and inorganic particles, the resin ratio of the light-shielding film being 87 vol% or more and 95 vol% or less.
[0013] The present invention also relates to a black light-shielding paint containing a resin, a colorant and inorganic particles, the light-shielding paint being characterized in that the light-shielding paint contains a dispersant having an amine value higher than its acid value. Effect of the Invention
[0014] According to the present invention, it is possible to provide an optical element, a light-shielding film, and a light-shielding paint which have a configuration in which a light-shielding film is formed on the end of a cemented lens having a chamfered portion which is susceptible to stress, and which do not crack even when subjected to severe thermal shock, and which have high washability and excellent anti-internal reflection performance. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic diagram showing an example of a conventionally known light-shielding film and a lens provided with the light-shielding film. [Diagram 2] 1 is a schematic cross-sectional view showing an interface state between a conventionally known light-shielding film and a lens on which the light-shielding film is formed. [Diagram 3] FIG. 1 is a schematic cross-sectional view of a conventionally known cemented lens. [Figure 4] 1 is an enlarged schematic cross-sectional view of an end surface of a cemented lens having a chamfered portion, which has been known in the art. [Diagram 5] FIG. 2 is an enlarged schematic diagram of an end face of a conventionally known cemented lens having no chamfer. [Figure 6] FIG. 2 is a cross-sectional schematic view of a cemented lens of the present invention. [Figure 7] 4 is an enlarged schematic cross-sectional view of an end face of a cemented lens having a chamfered portion and a rounded portion. FIG. [Figure 8A] 13 is an enlarged schematic cross-sectional view showing the length of a chamfered portion when the chamfered portion has a corner. FIG. [Figure 8B] 13 is an enlarged schematic cross-sectional view showing the length of a chamfered portion when the chamfered portion has a rounded portion. FIG. [Figure 9] 1 is a schematic cross-sectional view of an imaging device in which a lens unit (optical system) is mounted on an imaging unit. [Figure 10] FIG. 2 is a schematic diagram showing a method for measuring the internal reflectance. [Figure 11] FIG. 2 is a schematic cross-sectional view of a test piece used for evaluating thermal shock resistance. [Figure 12] FIG. 2 is an enlarged view of an end face of a test piece used for evaluating thermal shock resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] First, the role of the light-shielding film for optical elements will be described with reference to the drawings. FIG. 1 is a schematic diagram showing an example of a conventionally known light-shielding film and a lens provided with this light-shielding film. As shown in FIG. 1, the light-shielding film 1X is formed on an arbitrary outer peripheral portion of the lens 2X. Here, the light (incident light 3X) that does not hit the outer peripheral portion of the lens 2X among the light incident on the lens 2X is transmitted as transmitted light 4X. On the other hand, the light (incident light 5X) that hits the outer peripheral portion of the lens 2X among the light incident on the lens 2X hits the light-shielding film 1X provided on the outer peripheral portion of the lens 2X. If the light-shielding film 1X of FIG. 1 is not formed, the light that hits the outer peripheral portion of the lens 2X is internally reflected and goes outside the lens 2X as internally reflected light 6X that is unrelated to the image. This internally reflected light 6X causes flare, ghosts, and the like, which are factors that deteriorate the image. For this reason, it is necessary to provide the light-shielding film 1X on the outer peripheral portion of the lens 2X in order to prevent the occurrence of flare, ghosts, and the like. By providing the light-shielding film 1X, the amount of internally reflected light 6X that adversely affects the image is reduced, making it possible to prevent flare and ghosting.
[0017] The principle of internal reflection will be described in detail with reference to the drawings. FIG. 2 is a schematic diagram showing the traveling direction of the internally reflected light. FIG. 2 shows the state in which the light-shielding film 1X is applied to the outer peripheral surface of the lens 2X. As shown in FIG. 2, internal reflection mainly occurs at two interfaces, that is, the interface 7X of the incident light 3X passing through the lens 2X and the interface 8X of the light-shielding film 1X and the air. That is, when the incident light 3X passing through the lens 2 hits the interface 7X, the incident light 3X is divided into light reflected at the interface 7X (first reflected light 9X) and light transmitted through the light-shielding film 1X (transmitted light 10X). The transmitted light 10X is also reflected at the interface 8X. The reflected light at this time becomes the second reflected light 11X. Here, the first reflected light 9X can be reduced by bringing the refractive index of the light-shielding film 1X closer to that of the lens 2X or by making the refractive index of the light-shielding film 1X higher than that of the lens 2X. As the refractive index of glass increases, the light-shielding film is also required to have a high refractive index. The second reflected light 11X can be reduced by absorbing the transmitted light 10X. Colorants are used to efficiently absorb the transmitted light 10X into the light-shielding film.
[0018] In recent years, due to the bonding portion of the cemented lens having a difference in linear expansion coefficient, the thinning of the lens end face, and the increase in soft glass, the lens tends to be easily subjected to stress by the light-shielding film when the light-shielding film is formed on the outer periphery of the lens. The cemented lens will be described with reference to the drawings. FIG. 3 is a cross-sectional schematic diagram of a conventionally known cemented lens. Also, FIG. 4 and FIG. 5 are enlarged views of the dashed line portion in FIG. 3. FIG. 4 is a cross-sectional enlarged schematic diagram of the end face of the cemented lens having a chamfered portion. FIG. 5 is an enlarged schematic diagram of the end face of the cemented lens without a chamfered portion. The cemented lens is composed of a first optical element 12X, a second optical element 13X, a third optical element 14X provided between the first optical element 12X and the second optical element 13X for bonding, and a light-shielding film 1X formed on the end faces of the first optical element 12X, the second optical element 13X, and the third optical element 14X. In addition, the concave and convex of the first optical element 12X and the second optical element 13X may be reversed. As shown in FIG. 4, a cemented lens is often provided with a chamfered portion 15X on the cemented surface side to prevent the lenses from colliding with each other and breaking. If the chamfered portion 15X is present, the light-shielding film 1X accumulates in the groove of the chamfered portion 15X. Also, if there is no chamfered portion as shown in FIG. 5, the non-chamfered corner 16X of the first optical element 12X and the non-chamfered corner 16X of the second optical element 13X collide with each other, which is likely to cause defects such as lens chipping. For this reason, the cemented lens is provided with a chamfered portion 15 as shown in FIG. 4.
[0019] In recent years, optical elements are often used in cold climates or in scorching heat, where they are subject to large thermal shocks. Therefore, there is a need to reduce the stress on the lens caused by the light-shielding film. The cemented lens having the chamfered portion in FIG. 4 tends to accumulate the light-shielding film 1X at the chamfered portion 15X, and therefore, when a large thermal shock is applied, the stress is transmitted to the first optical element 12X or the second optical element 13X, which may cause the light-shielding film to peel off or the optical elements to crack or break.
[0020] In addition, after the light-shielding film is formed, the lens must be ultrasonically cleaned multiple times to remove minute contaminants that occur during the manufacturing process.The light-shielding film must be able to withstand ultrasonic vibrations during cleaning without peeling off at the interface with the lens.
[0021] Preferred embodiments of the present invention will now be described. First, a method for realizing an optical element having a light-shielding film formed on the end face of a cemented lens having a chamfered portion that is susceptible to stress, which does not crack the lens even when subjected to severe thermal shock and has high washability, will be described. Additionally, an optical instrument and an imaging device having the same will be described, and the light-shielding paint and light-shielding film of the present invention will be described.
[0022] [Materials for obtaining light-shielding films with high thermal shock resistance, washability, and internal anti-reflection performance] In order to suppress internal reflection, the light-shielding film needs to have a refractive index equal to or higher than that of the lens. In order to greatly improve the refractive index, it is necessary to add a large amount of highly refractive inorganic particles nano-dispersed in the resin. However, since inorganic particles have a high elastic modulus, adding a large amount of inorganic particles hardens the film itself, applying a large stress to the lens and deteriorating thermal shock resistance. In addition, adding a large amount of inorganic particles reduces adhesion and deteriorates washing resistance.
[0023] It is conceivable to add a soft resin in order to improve the thermal shock resistance. However, although the thermal shock resistance is improved, the adhesion of the light-shielding film is reduced, resulting in a deterioration in washing resistance.
[0024] In order to improve the washing resistance, it is necessary to improve the adhesion of the light-shielding film and increase the elastic modulus of the resin. However, if the elastic modulus of the resin is high, the thermal shock resistance deteriorates.
[0025] As described above, it is difficult to achieve thermal shock resistance, washing resistance, and anti-reflection performance at the same time, since these are contradictory elements.
[0026] The present inventors have thoroughly investigated methods for achieving high thermal shock resistance, cleaning resistance, and anti-internal reflection performance at the same time for optical elements having a cemented end surface of a chamfered lens, and have found that all of these can be achieved by setting the resin ratio in a light-shielding film containing at least resin and inorganic particles to be 87 vol% or more and 95 vol% or less.
[0027] That is, the optical element of the present invention is an optical element having a first optical element, a second optical element, a third optical element bonding the first optical element and the second optical element, and a light-shielding film containing resin and inorganic particles provided in contact with end faces of the first optical element, the second optical element, and the third optical element, wherein the first optical element and / or the second optical element have a chamfered portion on the bonding surface side, at least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, and the resin ratio of the light-shielding film is 87 vol% or more and 95 vol% or less.
[0028] If the resin ratio is less than 87 vol%, the internal reflection prevention performance is good, but the thermal shock resistance and cleaning resistance are deteriorated. Also, if the resin ratio exceeds 95 vol%, the thermal shock resistance and cleaning resistance are good, but the internal reflection prevention performance is deteriorated. Therefore, in a cemented lens having a chamfered portion, by setting the resin ratio to 87 vol% or more and 95 vol% or less, it is possible to achieve high thermal shock resistance, cleaning resistance, and internal reflection prevention performance all at the same time.
[0029] [Optical elements] FIG. 6 shows a cemented lens, which is an example of the optical element of the present invention. The cemented lens of the present invention comprises a first optical element 12, a second optical element 13, a third optical element 14 provided between the first optical element 12 and the second optical element 13 for bonding, and a light-shielding film 1 formed on the end faces of the first optical element 12, the second optical element 13, and the third optical element 14. The optical element of the present invention is an optical element used in, for example, optical equipment such as a lens barrel of a camera, video, or broadcasting equipment, and imaging devices such as a camera body, a video body, a surveillance camera, an in-vehicle camera, and a weather camera that may be used outdoors. The optical element of the present invention has the light-shielding film of the present invention on the surface of a substrate such as glass or plastic. The light-shielding film may be formed on the entire outer periphery of the substrate, or may be formed on a part of the outer periphery of the substrate. The light-shielding film of the present invention has a first portion in contact with the first optical element, a second portion in contact with the second optical element, and a third portion in contact with the third optical element, and it is preferable that the maximum thickness of the third portion is greater than the maximum thicknesses of the first and second portions. The internal reflection prevention performance and thermal shock resistance of the optical element are improved. It is also preferable that the optical element has a side surface formed so that the third portion is recessed relative to the first and second portions. Chipping of the lens of the optical element can be prevented.
[0030] The substrate of the lens or the like can be of any shape. For example, it may be concave, convex, or a combination of both. The outer periphery may be flat, have multiple steps, or have grooves. The substrate may be formed by bonding multiple substrates of the lens or the like. The outer periphery of the lens may have a straight line. The substrate of the lens or the like may be made of any material. For example, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, ZnO, Y2O3, La2O3, Nd2O3, Gd2O3, B2O3, Al2O3, TiO2, ZrO2, HfO2, SiO2, GeO, Nb2O5, Ta2O5, P2O5, Sb2O3, WO3, F2, etc. The constituents may be one type or a combination of multiple materials.
[0031] The curved portion of the optical element of the present invention will be described with reference to FIG. 7. FIG. 7 is an enlarged view of the dashed line portion of FIG. 6, and is a schematic enlarged cross-sectional view of the end face of a cemented lens having a chamfered portion and a curved portion. As shown in FIG. 7, the optical element of the present invention preferably has a curved portion 17 at the chamfered portion 15 on the cemented surface side of the first optical element 12 and / or the second optical element 13. By providing the curved portion 17, the light-shielding film 1 is easily allowed to flow out by its own weight when it is formed, and the light-shielding film 1 is less likely to accumulate in the groove of the chamfered portion. Since the light-shielding film 1 is less likely to accumulate in the groove of the chamfered portion, stress is less likely to occur even when a thermal shock is applied, and the thermal shock resistance is improved. In addition, the radius of curvature of the curved portion 17 of the present invention is preferably 0.05 mm or more and 1.0 mm or less, and more preferably 0.06 mm or more and 0.5 mm or less. If the radius of curvature is less than 0.05 mm, the light-shielding paint is less likely to flow out when the light-shielding film is formed, and the film thickness becomes thick, which may deteriorate the thermal shock resistance. Moreover, it is difficult to manufacture a tube with a radius of curvature exceeding 1.0 mm.
[0032] The length of the chamfered portion of the optical element of the present invention is preferably 0.05 mm or more and 0.35 mm or less, more preferably 0.1 mm or more and 0.35 mm or less. If the length of the chamfered portion is less than 0.05 mm, there is a risk of collision during lens processing, resulting in defects such as lens chipping. If the length of the chamfered portion exceeds 0.4 mm, the light-shielding film is likely to accumulate in the chamfered portion, and the thickness of the light-shielding film may increase, resulting in a risk of deterioration in thermal shock resistance. Here, the length of the chamfered portion refers to the length 71 from corner 72 to corner 72 when there is a corner 72 as shown in FIG. 8A. Also, if there is a rounded portion 74 in the chamfered portion as shown in FIG. 8B, it refers to the length 71 from vertex 73, which is the intersection point connecting the straight line portions, to vertex 73.
[0033] The end face in the present invention refers to the chamfered and rounded portions of the first optical element, the end portion (including the chamfered and / or rounded portions in some cases) of the second optical element, and the exposed surface end portion of the third optical element (see Figures 6 and 7). Usually, it refers to the outer peripheral surface of a cemented lens.
[0034] The maximum diameter of the optical element of the present invention is preferably 45 mm or more and 300 mm or less, more preferably 45 mm or more and 100 mm or less. A cemented lens having a maximum diameter of less than 45 mm may be too small and difficult to manufacture. In addition, if the maximum diameter of the optical element exceeds 300 mm, stress may be generated in the lens, and the thermal shock resistance may be deteriorated.
[0035] The difference in linear expansion coefficient between the first optical element of the present invention and the second optical element of the present invention is preferably 5 ppm or more and 20 ppm or less at -30°C to 70°C, more preferably 5 ppm or more and 13 ppm or less. It is practically difficult to make the difference in linear expansion coefficient between the first optical element and the second optical element of the present invention less than 5 ppm. Furthermore, if the difference in linear expansion coefficient between the first optical element and the second optical element of the present invention exceeds 20 ppm, stress is generated in the lens, which may deteriorate the thermal shock resistance. Note that the linear expansion coefficients are all values at -30°C to 70°C, and ppm is 10 ppm. -7 / ℃.
[0036] Examples of commercially available glass used for the substrate include S-LAM 2 (7.4 ppm), S-LAM60 (5.4 ppm), S-TIH53 (8.8 ppm), S-BSL 7 (7.2 ppm), S-NBM51 (6.5 ppm), L-BAL42 (7.2 ppm), S-FPL55 (13.6 ppm), S-FPL51 (13.1 ppm), S-FPM3 (11.5 ppm), S-FSL 5 (9 ppm), S-FPL53 (14.5 ppm), S-FPM4 (12.4 ppm), S-NSL36 (8 ppm), S-TIL6 (8.2 ppm), all manufactured by OHARA Corporation, and quartz (0.5 ppm). Furthermore, since equivalent products are commercially available from SCHOTT, HOYA, etc., these can also be used.
[0037] The third optical element 14 is a layer formed by hardening an adhesive, which is a precursor used for bonding glass lenses. The adhesive is required to be optically transparent, have high adhesive strength, and have a fast hardening speed, and acrylic, epoxy, and polyene polythiol hardening adhesives can be suitably used. A hardening initiator is added to these adhesives, and they can be hardened by heat or ultraviolet light, but hardening by heat may cause interface peeling or deformation of the surface shape. Therefore, it is preferable to use an ultraviolet-hardening adhesive as the adhesive of the third optical element 14. In addition, from the viewpoint of reducing the hardening shrinkage of the adhesive and adjusting the optical characteristics, it is also preferable to mix and disperse inorganic fine particles in the adhesive. In addition, it is preferable that the maximum thickness of the light-shielding film in contact with the third optical element is 20 μm or more and 180 μm or less. The first optical element 12 and the second optical element 13 may be provided with an anti-reflection coating (not shown).
[0038] The cemented lens is used as an optical system or as a part of an optical system in optical devices such as imaging devices (including cameras, videos, etc.), telescopes, binoculars, copiers, projectors, etc. As an example, FIG. 9 shows a schematic cross section of an imaging device 200 in which a lens unit (optical system having a plurality of lenses) 20 is mounted on an imaging unit 30. The cemented lens 21 (100) is disposed inside a housing 22 of the lens unit 20, and is fixed to the imaging unit 30 by a mount 23. The imaging unit 30 includes an imaging element 33 that receives light that has passed through the lens unit 20, and a shutter 32 in a housing 31. The imaging element 33 is disposed so that an optical axis 40 of the cemented lens 21 passes through its center. The imaging element 33 further includes a drive unit 34 that opens and closes the shutter 32, and a control unit 35 that controls the drive unit 34 and data reading from the imaging element 33.
[0039] [Light-shielding paint of the present invention] The material composition of the light-shielding coating material of the present invention and the method for producing the light-shielding coating material of the present invention will be described below.
[0040] <Material composition> (Main ingredient) The main agent contained in the light-shielding coating material of the present invention will now be described. The main component contained in the light-shielding coating material of the present invention can be any material that can form a light-shielding film. Examples of the main component contained in the light-shielding coating material of the present invention include epoxy resin, acrylic resin, urethane resin, acrylic urethane resin, phenol resin, melamine resin, polyester resin, alkyd resin, polyimide, etc.
[0041] The amount of the base agent contained in the light-shielding paint of the present invention is preferably 5% by weight or more and 87% by weight or less, more preferably 50% by weight or more and 85% by weight or less. If the amount of the base agent contained in the light-shielding paint of the present invention is less than 5% by weight, the light-shielding film becomes too hard and may crack due to thermal shock. If the amount of the base agent of the present invention exceeds 87% by weight, it may become difficult to increase the refractive index of the film. Note that all weight percentages are values based on solid content and do not include volatile components.
[0042] (Coloring agent) The colorant contained in the light-shielding coating material of the present invention will now be described. The colorant contained in the light-shielding coating of the present invention can be any material that can be colored. Examples of the colorant contained in the light-shielding coating of the present invention include dyes and pigments, and they may be used alone or in combination.
[0043] Examples of the dye include azo dyes, quinone dyes, cyanine dyes, cationic dyes, dicyanine dyes, indigo dyes, fulgide dyes, etc. Any color can be used, but examples include black, brown, yellow, red, blue, green, etc., and these may be used alone or in combination.
[0044] Examples of pigments include carbon black, titanium black, zirconium nitride, iron oxide, copper-iron-manganese composite oxide, and iron-chromium. Any shape of pigment can be used for the pigment contained in the light-shielding paint of the present invention. Examples of the shape of the pigment contained in the light-shielding paint of the present invention include a multi-layer structure in which spherical, irregular, plate-like, needle-like, star-like, chain-like, and plate-like particles are stacked. In addition, the pigment contained in the light-shielding paint of the present invention may be coated with other materials. The average particle size of the pigment contained in the light-shielding paint of the present invention is preferably 1 nm or more and 200 nm or less, and more preferably 5 nm or more and 50 nm or less. If the average particle size of the pigment contained in the light-shielding paint of the present invention is less than 1 nm, the paint may thicken. In addition, if the average particle size of the pigment of the present invention exceeds 200 nm, the scattering of the film may increase.
[0045] The amount of colorant added to the light-shielding coating of the present invention is preferably 1% by weight or more and 30% by weight or less, more preferably 2% by weight or more and 20% by weight or less. If the amount of colorant added to the light-shielding coating of the present invention is less than 1% by weight, the light entering the film may not be absorbed completely, and the internal reflection characteristics may deteriorate. If the amount of colorant added to the light-shielding coating of the present invention exceeds 30% by weight, the film may become too hard. Note that all weight percentages are based on the solid content and do not include volatile components.
[0046] The light-shielding paint of the present invention is black. Black is defined as the lightness (L * ) is less than 14. The lightness of the light-shielding coating material is preferably 10 or less, and more preferably 5 or less.
[0047] (Inorganic particles) The inorganic particles contained in the light-shielding coating material of the present invention will now be described. The average particle size of the inorganic particles contained in the light-shielding coating material of the present invention is preferably 2 nm to 250 nm, more preferably 50 nm to 200 nm, and even more preferably 100 nm to 180 nm. If the average particle size of the inorganic particles of the present invention exceeds 200 nm, the light-shielding film may become too scattered, resulting in a deterioration in appearance.
[0048] The d-line refractive index of the inorganic particles contained in the light-shielding coating material of the present invention is preferably 1.6 to 3.1, and more preferably 2.0 to 3.1. If the d-line refractive index is less than 1.6, a large amount of particles must be added to increase the refractive index of the light-shielding film of the present invention, which may increase the elastic modulus of the light-shielding film and deteriorate its thermal shock resistance.
[0049] The amount of inorganic particles contained in the light-shielding paint of the present invention is preferably 2% by weight or more and 60% by weight or less, and more preferably 5% by weight or more and 30% by weight or less. If the amount of inorganic particles contained in the light-shielding paint of the present invention is less than 2% by weight, the refractive index of the light-shielding film does not increase much, and the internal reflection prevention performance may decrease. If the amount of inorganic particles contained in the light-shielding paint of the present invention is more than 60% by weight, the elastic modulus of the light-shielding film of the present invention may become too high, and the thermal shock resistance may not be improved. Note that all weight percentages are values based on solid content and do not include volatile components.
[0050] The type of inorganic particles contained in the light-shielding coating of the present invention may be any metal or metal oxide as long as the d-line refractive index is 1.6 or more and 3.1 or less. Examples of inorganic particles having a d-line refractive index of 1.60 or more contained in the light-shielding coating of the present invention include red iron oxide (3.01), magnetite (2.42), rutile titanium oxide (2.72), anatase titanium oxide (2.52), zirconium oxide (2.05), cerium oxide (2.2), zinc oxide (2.1), tantalum pentoxide (2.16), aluminum nitride (1.9-2.2), tungsten oxide (2.2), niobium pentoxide (2.33), indium tin oxide (2.06), chromium oxide, and the like. Examples of these include titanium (2.24), diamond (2.42), aluminum oxide (1.63), cerium fluoride (1.63), yttrium oxide (1.87), magnesium oxide (1.74), hafnium oxide (1.95), lanthanum oxide (1.84), scandium oxide (1.89), europium oxide (1.90), molybdenum oxide (1.90), samarium fluoride (1.90), praseodymium oxide (1.92), silicon (3.4), and copper-iron-manganese composite oxide.
[0051] The inorganic particles having a d-line refractive index of 1.6 or more contained in the light-shielding coating material of the present invention may be of one type, or may contain a plurality of types, or may be in the form of a composite.
[0052] The inorganic particles contained in the light-shielding paint of the present invention may have any shape. Examples of the shape of the inorganic particles contained in the light-shielding paint of the present invention include a multi-layer structure in which spherical, amorphous, plate-like, needle-like, star-like, chain-like, and plate-like particles are stacked. The inorganic particles of the present invention may be coated with other materials. The inorganic particles contained in the light-shielding paint of the present invention may be one type or multiple types.
[0053] (hardening agent) The curing agent contained in the light-shielding paint of the present invention will be described. The curing agent contained in the light-shielding paint of the present invention can be any material as long as it can react with the main agent and harden. Examples include amine-based curing agents, isocyanate-based curing agents, and photoinitiators. The amount of the curing agent of the present invention added is preferably 1% by weight or more and 50% by weight or less, and more preferably 5% by weight or more and 40% by weight or less. If the amount of the curing agent of the present invention added is less than 1% by weight, the curing property may deteriorate and the washing resistance may deteriorate. In addition, if the amount of the curing agent added in the light-shielding paint of the present invention exceeds 50% by weight, the internal reflection property may deteriorate. Note that all weight percentages are based on the solid content and do not include volatile components.
[0054] (solvent) Next, the solvent contained in the light-shielding coating material of the present invention will be described. Any material may be used as the solvent. In addition, if the viscosity of the light-shielding paint is sufficiently low and it can be used as it is, there is no need to add a solvent. Examples of solvents include water, thinner, ethanol, isopropyl alcohol, n-butyl alcohol, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, toluene, xylene, acetone, cellosolves, glycol ethers, ether, hexane, cyclohexane, 1-butanol, methylcyclohexane, ethylcyclohexane, isohexane, benzyl alcohol, 2-ethyl-1-hexanol, butyl cellosolve, 1-butoxy-2-propanol, neopentane, solves, trichloroethylene, perchloroethylene, methanol, cellosolve acetate, mineral spirits, tetrahydrofuran, dioxane, N-methyl-2-pyrrolidone, ethyl lactate, and the like. These solvents may be used alone or in combination.
[0055] The preferred viscosity of the light-shielding coating of the present invention is 10 mPa·s or more and 10,000 mPa·s or less, and more preferably 30 mPa·s or more and 500 mPa·s or less. If the viscosity of the light-shielding coating is less than 10 mPa·s, there may be some areas where the coating thickness is thin after application. If the viscosity exceeds 10,000 mPa·s, the applicability of the light-shielding coating may decrease.
[0056] (Resin and resin ratio) The resin and resin ratio contained in the light-shielding paint of the present invention will be described. The resin refers to the sum of the main agent, hardener, coupling agent, dispersant, etc., and refers to the material excluding volatile components, inorganic particles, and colorants. The resin ratio refers to the sum of the resin excluding inorganic particles and colorants relative to the solid content. The resin ratio of the light-shielding paint of the present invention is 70% by weight or more and 84% by weight or less. If the resin ratio of the light-shielding paint of the present invention is less than 70% by weight, the thermal shock resistance and washing resistance are deteriorated. If the resin ratio of the light-shielding paint of the present invention exceeds 84% by weight, it becomes difficult to increase the refractive index of the film, and the internal reflection characteristics are deteriorated. The resin ratio can be obtained by dividing the weight of the film that disappears when the film is baked at 1000°C by the weight before baking. Resin ratio (wt%) = weight of film lost (g) / weight before baking (g) × 100 (Equation 1)
[0057] (Other additives) The light-shielding coating material of the present invention may contain any other additive. Examples of additives include curing accelerators, dispersants, defoamers, thixotropy-imparting agents, leveling agents, matting agents, preservatives, antibacterial agents, antifungal agents, UV absorbers, UV initiators, antioxidants, coupling agents, inorganic particles and organic fine particles for adjusting the color other than those mentioned above. Addition is made within a range that does not deteriorate the properties. In the present invention, it is preferable that the light-shielding coating material contains a dispersant whose amine value is higher than its acid value. In addition, the preferred range of the difference between the acid value and the amine value is 1 mgKOH / g or more and 100 mgKOH / g or less, more preferably 2 mgKOH / g or more and 30 mgKOH / g or less.
[0058] <<Method of manufacturing paint for application on the upper surface of optical equipment>> The method for producing the light-shielding coating material of the present invention will be described below. As a method for producing the light-shielding coating material of the present invention, any method can be used as long as it can disperse the inorganic particles of the present invention having a d-line refractive index of 2.0 or more and an average particle size of 200 nm or less, and the pigment to be added to the light-shielding coating material in the light-shielding coating material. Examples of the method include a bead mill, a ball mill, a jet mill, a three-roller mill, a planetary rotating device, a mixer, an ultrasonic disperser, a homogenizer, etc.
[0059] If the d-line refractive index is 2.0 or more and the average particle size exceeds 200 nm, the film may become scattered, resulting in a poor appearance.
[0060] [Light-shielding film of the present invention] The material composition of the light-shielding film of the present invention and the method for forming the light-shielding film will be described below. Material Composition The material composition of the light-shielding film of the present invention will be described below.
[0061] (Main ingredient) The main agent contained in the light-shielding film of the present invention will be described. The main agent used is the same as that listed in the above [Light-shielding paint] section. The amount of the main agent added to the light-shielding film of the present invention is preferably 5 vol% or more and 97 vol% or less, more preferably 40 vol% or more and 90 vol% or less. If the main agent contained in the light-shielding film of the present invention is less than 5 vol%, the light-shielding film may become too hard and film cracks may occur. If the main agent contained in the light-shielding film of the present invention exceeds 97 vol%, it may be difficult to increase the refractive index of the film.
[0062] (Coloring agent) The colorant contained in the light-shielding film of the present invention will be described. The amount of the colorant contained in the light-shielding film of the present invention is preferably 1 vol% or more and 30 vol% or less, more preferably 2 vol% or more and 20 vol% or less. If the amount of the colorant contained in the light-shielding film of the present invention is less than 1 vol%, the light entering the film may not be absorbed completely, and the internal reflection characteristics may deteriorate. Also, if the amount of the colorant contained in the light-shielding film of the present invention is more than 30 vol%, the film may become too hard.
[0063] The light-shielding film of the present invention is black, and its lightness (L * ) is less than 14. The lightness of the light-shielding film is preferably 10 or less, and more preferably 5 or less.
[0064] (Inorganic particles) The inorganic particles contained in the light-shielding film of the present invention will be described. The amount of inorganic particles contained in the light-shielding film of the present invention is preferably 2 vol% or more and 60 vol% or less, and more preferably 3 vol% or more and 30 vol% or less. If the amount of inorganic particles contained in the light-shielding film of the present invention is less than 2 vol%, the refractive index of the light-shielding film does not increase much, and the internal reflection prevention performance may be reduced. If the amount of inorganic particles contained in the light-shielding film of the present invention is more than 60 vol%, the thermal shock resistance may be deteriorated.
[0065] (hardening agent) Next, the curing agent contained in the light-shielding film of the present invention will be described. Any material can be used as the curing agent contained in the light-shielding film of the present invention as long as it can react with the main agent and harden. Examples include amine-based curing agents, isocyanate-based curing agents, and photoinitiators. The amount of the curing agent added to the light-shielding film of the present invention is preferably 1 vol% or more and 50 vol% or less, and more preferably 10 vol% or more and 40 vol% or less. If the amount of the curing agent added to the light-shielding film of the present invention is less than 1 vol%, the curing property may deteriorate and the washing resistance may deteriorate. Also, if the amount of the curing agent added to the light-shielding film of the present invention exceeds 50 vol%, the internal reflection property may deteriorate.
[0066] (resin ratio) The resin and resin ratio contained in the light-shielding film of the present invention will be described. The resin refers to the sum of the main agent, the curing agent, the coupling agent, the dispersant, etc., and refers to the material excluding the volatile component, the inorganic particles, and the colorant. The resin ratio indicates the ratio of the total resin excluding the inorganic particles and the colorant to the solid content. The resin ratio contained in the light-shielding film of the present invention must be 87 vol% or more and 95 vol% or less. If the resin contained in the light-shielding film of the present invention is less than 87 vol%, the thermal shock resistance and washing resistance are deteriorated. If the resin ratio contained in the light-shielding film of the present invention exceeds 95 vol%, it becomes difficult to increase the refractive index of the film, and the internal reflection characteristics are deteriorated. The resin ratio can be obtained by photographing the cross section of the film with a transmission electron microscope and calculating the ratio of the area excluding the inorganic particles and the colorant based on the area of the entire photographed image. Resin ratio (vol%) = Area excluding inorganic particles and colorants (cm 2) / total image area (cm 2 )×100...(Formula 2)
[0067] (Other additives) The light-shielding film of the present invention may contain any other additive. Examples of additives include a curing accelerator, a dispersant, an antifoaming agent, a thixotropic agent, a leveling agent, a matting agent, a preservative, an antibacterial agent, an antifungal agent, an ultraviolet absorber, an ultraviolet initiator, an antioxidant, a coupling agent, and inorganic particles and organic fine particles for adjusting the color other than those mentioned above. In the present invention, it is preferable that the light-shielding film contains a dispersant having an amine value higher than the acid value. In addition, the preferred range of the difference between the acid value and the amine value is 1 mgKOH / g or more and 100 mgKOH / g or less, more preferably 2 mgKOH / g or more and 30 mgKOH / g or less.
[0068] (Elastic modulus of light-shielding film) In recent years, lenses have tended to be more susceptible to stress when a light-shielding film is formed on the outer periphery of a lens due to the thinner bonded parts of cemented lenses and lens end faces, and the increase in soft glass. Lenses are also often used in cold regions or in scorching heat, where they are subject to large thermal shocks. Therefore, there is a need to reduce the stress on lenses caused by the light-shielding film. Note that the temperature in cold regions is assumed to be around -30°C.
[0069] In addition, after the light-shielding film is formed, the lens must be ultrasonically cleaned multiple times to remove extremely fine dirt that accumulates on the lens during the manufacturing process. Ultrasonic cleaning is carried out at room temperature, around 20°C. It is necessary that the light-shielding film does not peel off at the interface with the lens due to ultrasonic vibrations during cleaning.
[0070] For these reasons, the elastic modulus, which is a film property that can ensure thermal shock resistance and washing resistance, is required. From the viewpoint of thermal shock resistance of the light-shielding film in cold regions, the modulus of elasticity at -30°C is preferably 2500 MPa or more and 5100 MPa or less, more preferably 3000 MPa or more and 4900 MPa or less. If the modulus of elasticity of the light-shielding film at -30°C is less than 2500 MPa, the modulus of elasticity at room temperature also decreases, so that the washing resistance may deteriorate. By setting the resin ratio of the light-shielding film to 87 vol% or more and 95 vol% or less, it is possible to set the modulus of elasticity within a preferred range. If the modulus of elasticity of the light-shielding film at -30°C exceeds 5100 MPa, the lens may crack in a thermal shock test.
[0071] In addition, assuming that the light-shielding film is washed at room temperature of about 20° C., the modulus of elasticity of the light-shielding film at 20° C. is preferably 500 MPa or more and 3000 MPa or less, more preferably 1000 MPa or more and 2600 MPa or less. If the modulus of elasticity of the light-shielding film at 20° C. is less than 500 MPa, the washing resistance may deteriorate. If the modulus of elasticity of the light-shielding film at 20° C. exceeds 3000 MPa, the modulus of elasticity at −30° C. also increases, and the lens may crack in a thermal shock test.
[0072] <<Method of forming light-shielding film>> The light-shielding film of the present invention is preferably formed with an average thickness of 1 μm to 150 μm, more preferably 2 μm to 30 μm, on the end faces of the first optical element and the second optical element. The thickness of the light-shielding film at the chamfered portion is preferably 1 μm to 180 μm, more preferably 2 μm to 100 μm. If the thickness of the light-shielding film at the chamfered portion is less than 1 μm, the light-shielding film may become see-through, and the light-shielding performance may be reduced. If the thickness of the light-shielding film at the chamfered portion exceeds 180 μm, the stress on the lens increases, and the lens may crack when a thermal shock is applied. In addition, the maximum thickness of the light-shielding film at the portion in contact with the third optical element is preferably 20 μm to 180 μm. If the maximum thickness of the light-shielding film at the portion in contact with the third optical element is less than 20 μm, the light-shielding film may become see-through, and the light-shielding performance may be reduced. If the maximum thickness of the light-shielding film in the portion in contact with the third optical element exceeds 180 μm, the stress on the lens increases, and there is a risk that the lens may crack when subjected to thermal shock.
[0073] Any coating method and curing method can be used as long as the light-shielding coating material can be uniformly applied.
[0074] Examples of the application method of the light-shielding coating material of the present invention include brush application, spray application, dip coating, spin coating, transfer, inkjet, etc. The light-shielding film may be one-layered or multi-layered. The glass surface may be dry-surface-treated with UV ozone, plasma, excimer, etc., or wet-surface-treated with a coupling agent, etc.
[0075] The light-shielding film of the present invention may be cured by leaving it at room temperature or by accelerating heating with any heat. Examples of a method for curing by applying heat include a heating furnace, a heater, and infrared heating. The curing temperature is preferably from room temperature to 200°C, and more preferably from room temperature to 150°C. The light-shielding film of the present invention may be cured with UV light.
[0076] [Example] Preferred embodiments of the present invention will now be described. Various evaluations, preparation of light-shielding coating materials, and preparation of light-shielding films in Examples 1 to 31 were carried out by the following methods.
[0077] <Evaluation method> <Method of measuring elastic modulus> A viscoelasticity measuring device was used to measure the elastic modulus. The light-shielding film was adjusted to a size of 5 mm wide, 20 mm long, and 0.15 mm thick, dried for one day, and then baked at 40°C for 100 hours to prepare a sample for elastic modulus measurement. The prepared sample for elastic modulus measurement was set in a viscoelasticity measuring device (Rheogel-E4000 (UBM)) and the elastic modulus was measured at -30°C and 20°C. It is desirable that the elastic modulus of the light-shielding film at -30°C is 2500 MPa or more and 5100 MPa or less.
[0078] ◯ is a light-shielding film with an elastic modulus at -30°C of 3000 MPa or more and 4900 MPa or less, which can be said to have a good elastic modulus. △ is a light-shielding film with an elastic modulus at -30°C of 2500 MPa or more and less than 3000 MPa, or with an elastic modulus at -30°C of more than 4900 MPa and 5100 MPa or less, which can be said to be a relatively good light-shielding film. × is a light-shielding film with an elastic modulus at -30°C of more than 5100 MPa or with an elastic modulus at 30°C of less than 2500 MPa, which cannot be said to be a good light-shielding film.
[0079] ○: Light-shielding film with an elastic modulus of 3000MPa to 4900MPa at -30℃ △: Light-shielding film with modulus of elasticity at -30℃ of 2500MPa or more and less than 3000MPa, or modulus of elasticity at -30℃ of more than 4900MPa and less than 5100MPa ×: Light-shielding film with modulus of elasticity at -30°C of more than 5100 MPa or modulus of elasticity at 30°C of less than 2500 MPa
[0080] <Method of measuring internal reflectance> The internal reflectance was measured using a spectrophotometer (U-4100: Hitachi High-Tech) as shown in Figure 10. A triangular prism 50 was used as the measurement sample. The shape of the triangular prism 50 is such that the length of one side containing a right angle is 30 mm, the thickness is 10 mm, and the material is S-LAH53 (nd=1.8; manufactured by Ohara).
[0081] Figure 10 shows the measurement method when the incident angle b to the triangular prism 50 is 90°. The light emitted from the spectrophotometer is incident on the triangular prism 50 at an incident angle b = 90°. At this time, refraction of the light occurs due to the difference between the refractive index of air and the refractive index of the triangular prism 50. The incident angle after refraction is c = 68.13°. The angle e after refraction with respect to the incident angle d was calculated from the following formula (1). The incident angle c was also calculated from the angle e after refraction. n=sin d / sin e Equation (3)
[0082] Next, the light refracted by the triangular prism 50 hits the bottom surface of the triangular prism 50 and is reflected to exit the triangular prism 50. The intensity of this reflected light was detected by a detector in the visible light region of wavelengths from 400 nm to 700 nm. Note that the background was a sample in which the three surfaces, the bottom surface, the incident surface, and the reflecting surface, were mirror surfaces and nothing was applied to the bottom surface of the triangular prism 50, and the internal reflectance was measured when a film was formed on the bottom surface of the triangular prism 50, which had three mirror surfaces, the bottom surface, the incident surface, and the reflecting surface. The internal reflectance was measured by measuring the internal reflection of visible light from 400 nm to 700 nm at 1 nm intervals, and the average value of the results was recorded. The internal reflectance was evaluated according to the following criteria: ◯ is an excellent film with an internal reflection of less than 40%, △ is a film with slightly poor internal reflection but no problems with an internal reflection of 40% or more but less than 60%, and × is a film with poor optical properties with an internal reflection of 60% or more. ○: Internal reflectance is less than 40% △: Internal reflectance is 40% or more and less than 60% ×: Internal reflectance is 60% or more
[0083] <Method of evaluating thermal shock resistance> FIG. 11 shows a schematic cross-sectional view of a test piece used to evaluate thermal shock resistance. FIG. 12 shows an enlarged end view of a test piece used to evaluate thermal shock resistance. For the evaluation of thermal shock resistance, two circular monitor glasses, a first monitor glass 51 and a second monitor glass 52, were bonded together with an adhesive 53 as shown in FIG. 11. The outer diameter of the first monitor glass and the thickness of the second monitor glass were each 5 mm, and the outer diameter was changed for each example and comparative example. As shown in FIG. 12, the shape of the chamfered portion 15 and the rounded portion 17 were provided, and the size was changed for each example and comparative example. As shown in FIG. 12, the length of the chamfered portion 15 of the light-shielding film 1 was changed for each example and comparative example. The thickness of the light-shielding film 1 on the outer periphery of the first monitor glass 51 and the second monitor glass 52 was changed for each example and comparative example. The outer periphery of the first monitor glass 51 and the second monitor glass 52 was chamfered with #1200. The prepared test pieces were left in an environment of -50°C for 30 minutes, and then left in an environment of 60°C for 30 minutes, and this constituted one set, and 10 cycles were repeated to apply thermal shock. The thermal shock resistance was evaluated according to the following criteria: ○ indicates an optical element with no problem in thermal shock resistance, △ indicates slight changes in the light-shielding film but within a range that is not problematic, and × indicates an optical element with problems in thermal shock resistance due to cracks or poor appearance. ○: No change in the light-shielding film or glass △: Some changes were observed in the light-shielding film, but this was within the range that did not cause any problems. ×: Cracks or defects in appearance occurred in the light-shielding film or glass
[0084] <Method for evaluating washability> To evaluate the cleaning resistance, a test piece was used in the same manner as in the evaluation of thermal shock resistance, in which a first monitor glass 51 and a second monitor glass 52 shown in FIG. 11 were bonded together with an adhesive 53, and a light-shielding film 1 was formed on the outer periphery to a thickness of approximately 4 μm.
[0085] The prepared test piece was placed in water and subjected to ultrasonic cleaning for 5 minutes, and then dried. Ultrasonic cleaning was performed 5 times. The cleaning resistance was evaluated according to the following criteria. ○ is a light-shielding film with no peeling and no color change in the lens interior, and no problem. △ is a light-shielding film with no peeling and color change in the lens interior, but not problematic. × is a light-shielding film with peeling and problematic. ○: No peeling, no color change inside the lens △: No peeling, color change inside the lens ×: Peeling
[0086] Productivity Evaluation For the evaluation of productivity, a test piece was used in the same manner as for the evaluation of thermal shock resistance, in which a first monitor glass 51 and a second monitor glass 52 shown in FIG. 11 were bonded together with an adhesive 53, and a light-shielding film 1 was formed on the outer periphery to a thickness of about 4 μm. 100 test pieces were prepared, and the lens end faces were visually checked for chipping or the like. Lenses in which not one of the 100 pieces has a defect such as chipping are optical elements with high productivity. Lenses in which one or two of the 100 pieces have chipping are generally optical elements with good productivity. Lenses in which three or more of the 100 pieces have chipping are optical elements with poor productivity. ○: Not even one defective sheet out of 100 sheets △: 1 to 2 pieces out of 100 are chipped ×: 3 or more sheets are missing out of 100 sheets
[0087] Color Evaluation For the evaluation of color, a test piece was used in which a light-shielding film 1 was formed with a thickness of about 20 μm on an arbitrary glass substrate. The color of the test piece was measured with a color difference meter to measure the lightness L * The measurement was performed. ○ indicates L * A film with a L value of less than 5 can be said to have a high blackness. * A film with a L value of 5 or more and less than 14 can be said to be black. * A film with a color of 14 or more cannot be considered black. ○: Film with high blackness △: Black film ×: Film that is not black
[0088] <Method of measuring average particle size> The average particle size was measured using a dynamic light scattering device (Zeta sizer Neo MPT-2: Sysmex). Inorganic particles diluted with a solvent were placed in a cell, and the average of 20 measurements was detected at a voltage of 5 mV. The average particle size was taken as the peak value in the number distribution. The average particle size was evaluated according to the following criteria. ○ indicates that the average particle size is 200 nm or less, and that the light-shielding film has little scattering and is excellent. × indicates that the average particle size is more than 200 nm, and that the light-shielding film has large scattering and cannot be said to be a good light-shielding film. ○: Average particle size is 200 nm or less ×: Average particle size exceeds 200 nm
[0089] <Method of Measuring Film Thickness> The film thickness of the optical element was measured by polishing the cut surface of the evaluation sample and measuring it with a field emission scanning electron microscope (ULTRA55, manufactured by Carl Zeiss).
[0090] Here, the film thicknesses in Tables 1 to 6 indicate the maximum film thicknesses of the light-shielding film in the portion in contact with the third optical element.
[0091] Example 1 <Adjustment of light-shielding paint> In Example 1, a light-shielding paint was prepared by the following method. 300g of epoxy resin A, which is the main component, 40g of colorant A, 200g of inorganic particles A, 20g of coupling agent A, 60g of dispersant A, and 400g of solvent A were weighed. All of the weighed raw materials were placed in a container and stirred with a stirring blade for 20 minutes to obtain a pre-dispersion. The pre-dispersion was stirred with a bead mill for 180 minutes to obtain the light-shielding paint of Example 1.
[0092] Toluene was used as solvent A. Rutile-type titanium oxide was used as inorganic particle A with a d-line refractive index of 2.0 or more and an average particle size of 200 nm or less. Carbon black was used as colorant A. DISPERBYK2155 (BYK Japan) was used as dispersant A. Bisphenol A-type epoxy resin (jER828; Mitsubishi Chemical) was used as epoxy resin A. As coupling agent A, an epoxy-based silane coupling agent (KBM403; Shin-Etsu Silicones) was used.
[0093] Inorganic particles A include TTO-51(A) (Ishihara Sangyo Kaisha), TTO-51(C) (Ishihara Sangyo Kaisha), TTO-55(A) (Ishihara Sangyo Kaisha), TTO-55(B) (Ishihara Sangyo Kaisha), TTO-55(C) (Ishihara Sangyo Kaisha), TTO-55(D) (Ishihara Sangyo Kaisha), STR-100N (Sakai Chemical Industry), STR-100A-LP (Sakai Chemical Industry), STR-100C-LP (Sakai Chemical Industry), STR-100W-LP (Sakai Chemical Industry), STR-100C-LF (Sakai Chemical Industry), STR-100W-OTS (Sakai Chemical Industry), and STR-100W(G). Materials selected from Sakai Chemical Industry Co., Ltd., STR-40OTS (Sakai Chemical Industry Co., Ltd.), MT-01 (Teika), MT-10EX (Teika), MT-05 (Teika), MT-100S (Teika), MT-100TV (Teika), MT-100Z (Teika), MT-150EX (Teika), MT-150W (Teika), MT-100AQ (Teika), MT-100WP (Teika), MT-100SA (Teika), and MT-100HD (Teika) were used.
[0094] The colorants used were materials selected from the following: #2650 (Mitsubishi Chemical), #2600 (Mitsubishi Chemical), #2350 (Mitsubishi Chemical), #2300 (Mitsubishi Chemical), #1000 (Mitsubishi Chemical), #980 (Mitsubishi Chemical), #970 (Mitsubishi Chemical), #960 (Mitsubishi Chemical), #950 (Mitsubishi Chemical), #850 (Mitsubishi Chemical), MCF88 (Mitsubishi Chemical), MA600 (Mitsubishi Chemical), #750B (Mitsubishi Chemical), #650B (Mitsubishi Chemical), MA100 (Mitsubishi Chemical), and MA220 (Mitsubishi Chemical).
[0095] <Preparation of light-shielding film> In Example 1, the light-shielding film was prepared by the following method. 180 g of hardener A was added to the total amount of the light-shielding paint, and the mixture was stirred for 30 minutes with a roll coater. An amine-based hardener was used as hardener A.
[0096] The following amine-based hardeners were used: ADEKA HARDENER EH-6019 (ADEKA), ADEKA HARDENER EH-6024 (ADEKA), ADEKA HARDENER EH-6028 (ADEKA), ADEKA HARDENER EH-479 (ADEKA), ADEKA HARDENER EH-451N (ADEKA), ADEKA HARDENER EH-4602 (ADEKA), ADEKA HARDENER EH2300 (ADEKA), ADEKA HARDENER EH3427A (ADEKA), ADEKA HARDENER EH-4024W (ADEKA), ST1 (Mitsubishi Chemical), ST12 (Mitsubishi Chemical), ST14 (Mitsubishi Chemical), ST15 (Mitsubishi Chemical), H3 (Mitsubishi Chemical), H30 (Mitsubishi Chemical), FL11 (Mitsubishi Chemical), FL11W (Mitsubishi Chemical), SA1 (Mitsubishi Chemical).
[0097] The mixture of the obtained light-shielding paint and the hardener was applied to a glass or lens for evaluation in a predetermined thickness and dried at room temperature for 60 minutes. After drying, the film was hardened in a thermostatic oven at 40° C. for 8 hours to obtain the film of Example 1.
[0098] The first monitor glass was S-FPL53 (manufactured by Ohara, linear expansion coefficient 14.5 ppm).
[0099] The second monitor glass was made of quartz S-FPL53 (manufactured by Toray, linear expansion coefficient 0.5 ppm).
[0100] <Preparation of samples for evaluating thermal shock resistance, washing resistance, and productivity> In preparing samples for evaluating thermal shock resistance, cleaning resistance, and productivity, S-FPL55 (manufactured by Ohara, linear expansion coefficient 13.6 ppm) was used for the first monitor glass. The first monitor glass was processed so that the diameter of the optical element was 65 mm, the length of the chamfer of the first optical element was 0.3 mm, and the radius of curvature of the rounded portion was 0.3 mm. Quartz S-FPL53 (manufactured by Toray, linear expansion coefficient 0.5 ppm) was used for the second monitor glass. The first monitor glass was processed so that the diameter of the optical element was 65 mm, the length of the chamfer of the first optical element was 0.3 mm, and the radius of curvature of the rounded portion was 0.3 mm. UT20V (manufactured by Kaneda) was used as the adhesive, and was cured with UV light. The difference in linear expansion coefficient between the first optical element and the second optical element was 14 ppm.
[0101] (Examples 2 to 31) In Examples 2 to 31, light-shielding films were produced in the same manner as in Example 1, except that the materials and conditions in Tables 1 to 6 were used.
[0102] The same base agent, coupling agent, dispersant, solvent, and curing agent were used in all of the examples and comparative examples.
[0103] Iron oxide (TM Red 8270; Dainichiseika Color & Chemicals) was used for inorganic particle B. Zirconia (Zircostar ZP-153; Nippon Shokubai) was used for inorganic particle C. Black dye (VALIFAST BLACK 3810; Orient Chemical) was used for colorant B.
[0104] Denacol EX-211 (Nagase Chemtex) was used for epoxy resin B. Denacol EX-321L (Nagase Chemtex) was used for epoxy resin C. Denacol EX-121 (Nagase Chemtex) was used for epoxy resin D. jER152 (Mitsubishi Chemical) was used for epoxy resin E.
[0105] [Table 1]
[0106] [Table 2]
[0107] [Table 3]
[0108] [Table 4]
[0109] [Table 5]
[0110] [Table 6]
[0111] Evaluation Results The heat shock resistance, washing resistance, internal reflectance, productivity (defective rate), elastic modulus, color, and average particle size of the light-shielding films of Examples 1 to 31 were evaluated by the above-mentioned methods. The results are shown in Tables 7 to 12.
[0112] As evaluation results, it is preferable that slight changes are observed in the light-shielding film in the thermal shock resistance test, but within a range that is not problematic. It is also preferable that there is no peeling or color change in the lens interior in the washing resistance test. It is also preferable that the internal reflectance is less than 60%. It is also preferable that the productivity is such that no more than 2 pieces out of 100 pieces are chipped. It is also preferable that the elastic modulus at -30°C is 2500 MPa or more and 5100 MPa or less. It is also preferable that the color is L * It is preferable that the average particle size is less than 14. It is also preferable that the average particle size is 200 nm or less.
[0113] In Example 1, a light-shielding paint was prepared using an epoxy resin, a colorant, inorganic particles, a coupling agent, a dispersant, and a solvent. A mixed solution was prepared by mixing the prepared light-shielding paint with a curing agent, and this was applied to each evaluation test piece to form a light-shielding film, and the thermal shock resistance, washing resistance, internal reflectance, productivity, elastic modulus, color, and average particle size were evaluated. As shown in Table 7, the thermal shock resistance was good with no change observed. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. In addition, the internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0114] In Example 2, a light-shielding film with a resin ratio of 95 vol % was used, as compared with Example 1. As shown in Table 7, no change was observed in the thermal shock resistance, and the film was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was 40% or more and less than 60%, and was generally good. Furthermore, no chipping occurred, and the productivity was good. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0115] In Example 3, a light-shielding film with a resin ratio of 89 vol % was used, as compared with Example 1. As shown in Table 7, no change was observed in the thermal shock resistance, and it was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was 40% or more and less than 60%, and was generally good. Furthermore, no chipping occurred, and the productivity was good. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and it was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0116] In Example 4, an optical element without a radius was used, unlike Example 1. As shown in Table 7, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, with regard to productivity, one or two small chips occurred, but this was within an acceptable range. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0117] In contrast to Example 1, Example 5 used an optical element with a radius of curvature of 0.05 mm. As shown in Table 7, the thermal shock resistance was good with no change observed. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. The elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0118] In Example 6, an optical element with a radius of curvature of 0.2 mm was used, unlike Example 1. As shown in Table 8, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0119] In Example 7, an optical element with a radius of curvature of 1.0 mm was used, unlike Example 1. As shown in Table 8, no change was observed in the thermal shock resistance, and it was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, and it was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and it was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0120] In Example 8, an optical element with a radius of curvature of 1.1 mm was used, unlike Example 1. As shown in Table 8, no change was observed in the thermal shock resistance, and it was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, and it was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and it was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0121] In Example 9, an optical element with a chamfered portion having a length of 0.05 mm was used, unlike Example 1. As shown in Table 8, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, productivity was within an acceptable range, with one or two small chips occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0122] In contrast to Example 1, Example 10 used an optical element with a chamfered portion having a length of 0.35 mm. As shown in Table 8, the thermal shock resistance was good with no change observed. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. The elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0123] In Example 11, an optical element having a chamfered portion with a length of 0.4 mm was used, unlike Example 1. As shown in Table 9, a slight change in color was observed in thermal shock resistance, but it was within an acceptable range. In addition, in terms of cleaning resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. The elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. In addition, the color was L * The value was less than 5, which indicated that the film was in good condition. Moreover, the average particle size was good, being 200 nm or less.
[0124] In Example 12, an optical element having a maximum diameter of 5 mm was used in contrast to Example 1. As shown in Table 9, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0125] In Example 13, an optical element having a maximum diameter of 300 mm was used in contrast to Example 1. As shown in Table 9, slight changes were observed in thermal shock resistance, but within an acceptable range. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. The elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0126] In Example 14, an optical element having a maximum diameter of 4 mm was used in contrast to Example 1. As shown in Table 9, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less. Since the lens was small, it took a long time to bond the lenses together.
[0127] In Example 15, an optical element having a maximum diameter of 310 mm was used in comparison with Example 1. As shown in Table 9, slight changes were observed in thermal shock resistance, but within an acceptable range. Furthermore, in terms of cleaning resistance, no peeling was observed, but slight color changes were observed in the lens interior, but within an acceptable range. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0128] In Example 16, unlike Example 1, an optical element was used in which the difference in linear expansion coefficient between the first and second optical elements was 5 ppm. The first monitor glass was S-FPL55 (manufactured by Ohara, linear expansion coefficient 13.6 ppm), and the second monitor glass was TIH53 (manufactured by Ohara, linear expansion coefficient 8.8 ppm). As shown in Table 10, no change was observed in thermal shock resistance, and the result was good. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, and the result was good. In addition, the productivity was good, with no chipping occurring. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0129] In Example 17, unlike Example 1, an optical element was used in which the difference in linear expansion coefficient between the first and second optical elements was 14 ppm. The first monitor glass was S-FPL53 (manufactured by Ohara, linear expansion coefficient 14.5 ppm), and the second monitor glass was quartz (manufactured by Toray, linear expansion coefficient 0.5 ppm). As shown in Table 10, slight changes were observed in thermal shock resistance, but within a range that was not problematic. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and it was a good film. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0130] In Example 18, unlike Example 1, an optical element was used in which the difference in linear expansion coefficient between the first and second optical elements was 4 ppm. The first monitor glass was S-FPM3 (manufactured by OHARA, linear expansion coefficient 11.5 ppm), and the second monitor glass was S-LAM2 (manufactured by OHARA, linear expansion coefficient 7.4 ppm). As shown in Table 10, no change was observed in thermal shock resistance, and the result was good. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0131] In Example 19, unlike Example 1, an optical element was used in which the difference in linear expansion coefficient between the first and second optical elements was 0.1 ppm. The first monitor glass was S-LAH65 (manufactured by Ohara, linear expansion coefficient 6.0 ppm), and the second monitor glass was S-LAH53 (manufactured by Ohara, linear expansion coefficient 5.9 ppm). As shown in Table 10, there was no change in thermal shock resistance and it was good. In addition, the washing resistance was good with no peeling and no change in the color of the lens interior. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0132] In Example 20, the light-shielding film used in Example 1 was adjusted by wiping off the grooves so that the film thickness was 20 μm. As shown in Table 10, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0133] In Example 21, the light-shielding film in Example 1 was adjusted by applying multiple coats to the grooves so that the film thickness was 180 μm. As shown in Table 11, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling occurred, and the color of the lens interior changed slightly, but this was within an acceptable range. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L *The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0134] In Example 22, the light-shielding coating material was wiped off to adjust the thickness of the light-shielding film to 18 μm, as compared with Example 1. As shown in Table 11, the thermal shock resistance was good with no change observed. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0135] In Example 23, the light-shielding coating material was applied in layers to adjust the thickness of the light-shielding film to 190 μm, as compared to Example 1. As shown in Table 11, slight changes were observed in the thermal shock resistance, but within an acceptable range. In addition, in terms of wash resistance, no peeling was observed, but the color of the lens interior changed slightly, but within an acceptable range. The internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0136] In Example 24, an optical element was used in which the modulus of elasticity of the light-shielding film at -30°C was adjusted to 3000 MPa, as compared to Example 1. As shown in Table 11, no change was observed in the thermal shock resistance, which was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the modulus of elasticity at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L *The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0137] In Example 25, an optical element was used in which the modulus of elasticity of the light-shielding film at -30°C was adjusted to 4900 MPa, as compared to Example 1. As shown in Table 11, slight changes were observed in the thermal shock resistance, but within an acceptable range. In addition, in terms of washing resistance, no peeling or color change was observed in the lens interior. The internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. The modulus of elasticity at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0138] In Example 26, an optical element was used in which the modulus of elasticity of the light-shielding film at -30°C was adjusted to 2500 MPa, as compared to Example 1. As shown in Table 12, no change was observed in the thermal shock resistance, which was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the modulus of elasticity at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0139] In Example 27, an optical element was used in which the modulus of elasticity of the light-shielding film at -30°C was adjusted to 5100 MPa, as compared to Example 1. As shown in Table 12, slight changes were observed in the thermal shock resistance, but within an acceptable range. In addition, in terms of washing resistance, no peeling or color change was observed in the interior of the lens. The internal reflectance was less than 40%, which was good. In addition, the productivity was good with no chipping. The modulus of elasticity at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. In addition, the color was L *The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0140] In Example 28, unlike Example 1, a light-shielding film using inorganic particles B was used. As shown in Table 12, no change was observed in thermal shock resistance, and the film was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0141] In Example 29, unlike Example 1, a light-shielding film using inorganic particles C was used. As shown in Table 12, no change was observed in thermal shock resistance, and the film was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0142] In Example 30, a light-shielding film using colorant B was used in contrast to Example 1. As shown in Table 12, no change was observed in the thermal shock resistance, and the film was good. Furthermore, in terms of washing resistance, no peeling or color change in the lens interior was observed. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good, with no chipping occurring. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and the film was good. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less. In Example 31, a light-shielding film was used that used dispersant B, which has an amine value / acid value of less than 1, as compared to Example 1. As shown in Table 12, no change was observed in the thermal shock resistance, which was good, but the internal appearance was slightly deteriorated, but within an acceptable range. In addition, in terms of washing resistance, no peeling or color change in the internal appearance of the lens was observed. The internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was in good condition with a value of less than 5. The average particle size was 200 nm or more, which was a deterioration, but was within the range of no problem.
[0143] [Table 7]
[0144] [Table 8]
[0145] [Table 9]
[0146] [Table 10]
[0147] [Table 11]
[0148] [Table 12]
[0149] (Comparative Examples 1 to 2) In Comparative Examples 1 and 2, a light-shielding film was produced in the same manner as in Example 1 except that the materials and conditions in Table 13 were used.
[0150] Table 13 shows the materials and mixing ratios of the paint and hardener in Comparative Examples 1 and 2. Table 14 shows the evaluation results of Comparative Examples 1 and 2 in which the coating material and curing agent in Table 13 were used. In Comparative Example 1, a light-shielding film with a resin ratio of 86 vol % was used in comparison with Example 1. As shown in Table 14, the thermal shock resistance showed that the lens cracked. Furthermore, the cleaning resistance showed that peeling occurred. Furthermore, the internal reflectance was less than 40%, which was good. Furthermore, the productivity was good with no chipping. Furthermore, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, which was a good film. Furthermore, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0151] In Comparative Example 2, a light-shielding film with a resin ratio of 96 vol % was used in comparison with Example 1. As shown in Table 14, no change was observed in the thermal shock resistance, and it was good. In addition, in terms of washing resistance, no peeling or color change in the lens interior was observed. In addition, the internal reflectance was poor, exceeding 60%. In addition, the productivity was good, with no chipping occurring. In addition, the elastic modulus at -30°C was 3000 MPa or more and 4900 MPa or less, and it was a good film. In addition, the color was L * The film was excellent, with a value of less than 5. The average particle size was also excellent, being 200 nm or less.
[0152] [Table 13]
[0153] [Table 14] [Industrial Applicability]
[0154] The optical element, light-shielding film, and light-shielding paint of the present invention can be used in the lens barrels of optical devices such as cameras, videos, and broadcasting equipment, as well as in camera bodies, video bodies, surveillance cameras, vehicle-mounted cameras, weather cameras, and other devices that may be used outdoors.
[0155] The disclosure of this embodiment includes the following configurations and methods. [Configuration 1] A first optical element; and A second optical element; and a third optical element bonded between the first optical element and the second optical element; and an optical element having a light-shielding film including a resin and inorganic particles provided in contact with end faces of the first optical element, the second optical element, and the third optical element, the first optical element and / or the second optical element has a chamfer on the bonding surface side; At least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, An optical element characterized in that the resin ratio of the light-shielding film is 87 vol % or more and 95 vol % or less. [Configuration 2] The optical element according to configuration 1, wherein the first optical element and the second optical element have a chamfered portion on the bonding surface side, and the first optical element and the second optical element having the chamfered portion have a rounded portion on the bonding surface side. [Configuration 3] the light-shielding film has a first portion in contact with the first optical element, a second portion in contact with the second optical element, and a third portion in contact with the third optical element; 3. The optical element according to embodiment 1 or 2, wherein the maximum thickness of the third portion is greater than the maximum thicknesses of the first portion and the second portion. [Configuration 4] The optical element according to configuration 3, wherein the third portion has a side surface formed to be recessed relative to the first portion and the second portion. [Configuration 5] 5. The optical element according to any one of configurations 1 to 4, wherein the length of the chamfered portion of the first optical element is not less than 0.05 mm and not more than 0.35 mm. [Configuration 6] 6. The optical element according to any one of configurations 1 to 5, wherein the maximum diameter of the optical element is 45 mm or more and 300 mm or less. [Configuration 7] 7. The optical element according to any one of configurations 1 to 6, wherein the difference in linear expansion coefficient between the first optical element and the second optical element is 5 ppm or more and 20 ppm or less. [Configuration 8] 8. The optical element according to any one of configurations 1 to 7, wherein the maximum thickness of the light-shielding film at the portion in contact with the third optical element is 20 μm or more and 180 μm or less. [Configuration 9] 9. The optical element according to any one of configurations 1 to 8, wherein the radius of curvature of the rounded portion is not less than 0.05 mm and not more than 1.0 mm. [Configuration 10] 10. The optical element according to any one of configurations 1 to 9, wherein the modulus of elasticity of the light-shielding film at −30° C. is 2500 MPa or more and 5100 MPa or less. [Configuration 11] 11. The optical element according to any one of configurations 1 to 10, wherein the light-shielding film contains a dispersant having an amine value higher than its acid value. [Configuration 12] An optical device comprising a housing and the optical element according to any one of configurations 1 to 11 disposed inside the housing. [Configuration 13] 12. An imaging device comprising: a housing; an optical system including the optical element according to claim 1 disposed inside the housing; and an imaging element that receives light incident through the optical system. [Method 1] A method for manufacturing an optical element, comprising the steps of: A step of bonding the first optical element and the second optical element with an adhesive that is a precursor of a third optical element; applying a light-shielding coating material to end faces of the first optical element, the second optical element, and the third optical element, and curing the coating material to form a light-shielding film; having The light-shielding film contains a resin and inorganic particles, the first optical element and / or the second optical element has a chamfer on the bonding surface side; At least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, A method for producing an optical element, wherein the resin ratio of the light-shielding film is 87 vol % or more and 95 vol % or less. [Configuration 14] a light-shielding film provided in contact with end faces of a first optical element, a second optical element, and a third optical element that bonds the first optical element and the second optical element, the light-shielding film contains a resin and inorganic particles and is black in color; The light-shielding film has a resin ratio of 87 vol % or more and 95 vol % or less. [Configuration 15] 15. The light-shielding film according to configuration 14, wherein the maximum thickness of the light-shielding film at a portion in contact with the third optical element is 20 μm or more and 180 μm or less. [Configuration 16] 16. The light-shielding film according to aspect 14 or 15, wherein the light-shielding film has an elastic modulus at −30° C. of 2500 MPa or more and 5100 MPa or less. [Configuration 17] 17. The light-shielding film according to any one of configurations 14 to 16, wherein the light-shielding film contains a dispersant having an amine value higher than its acid value. [Configuration 18] A black light-shielding paint containing a resin, a colorant and inorganic particles, the light-shielding paint comprising a dispersant having an amine value higher than its acid value. [Explanation of symbols]
[0156] 1X, 1. Light-shielding film 2X lens 3X.Incoming light 4X.Transmitted light 5X.Incoming light 6X. Internally reflected light 7X.Interface 8X.Interface 9X. First reflected light 10X.Transmitted light 11X. Second reflected light 12X, 12. First Optical Element 13X, 13. Second Optical Element 14X, 14.Third Optical Element 15X, 15. Chamfered section 16X. No chamfered corners 17. R Section 20. Lens unit (optical system) 21.(100) cemented lens 22. Housing tube 23. Mount 30. Imaging unit 31. Cabinet 32. Shutter 33. Image sensor 34. Drive unit 35. Control Unit 40. Optical axis 200. Imaging device 50. Triangular Prism 51. First monitor glass 52. Second monitor glass 53. Glue 71. Length of chamfer 72. Corner 73. Vertex 74. R Club
Claims
1. A first optical element; and A second optical element; and a third optical element that bonds the first optical element and the second optical element; and an optical element having a light-shielding film including a resin and inorganic particles and provided in contact with end faces of the first optical element, the second optical element, and the third optical element, the first optical element and / or the second optical element has a chamfer on a bonding surface side; At least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, An optical element characterized in that the resin ratio of the light-shielding film is 87 vol % or more and 95 vol % or less.
2. the first optical element and the second optical element have a chamfered portion on the bonding surface side, The optical element according to claim 1 , wherein the first optical element and the second optical element having the chamfered portion have a rounded portion on the bonding surface side.
3. the light-shielding film has a first portion in contact with the first optical element, a second portion in contact with the second optical element, and a third portion in contact with the third optical element; The optical element according to claim 1 , wherein the maximum thickness of the third portion is greater than the maximum thicknesses of the first portion and the second portion.
4. The optical element according to claim 3 , wherein the third portion has a side surface formed so as to be recessed with respect to the first portion and the second portion.
5. The optical element according to claim 1 , wherein the length of the chamfer of the first optical element is not less than 0.05 mm and not more than 0.35 mm.
6. 2. The optical element according to claim 1, wherein the maximum diameter of the optical element is 45 mm or more and 300 mm or less.
7. 2. The optical element according to claim 1, wherein a difference in linear expansion coefficient between the first optical element and the second optical element is 5 ppm or more and 20 ppm or less.
8. 2. The optical element according to claim 1, wherein the maximum thickness of the light-shielding film at a portion in contact with the third optical element is 20 μm or more and 180 μm or less.
9. 2. The optical element according to claim 1, wherein the radius of curvature of the rounded portion is equal to or greater than 0.05 mm and equal to or less than 1.0 mm.
10. 2. The optical element according to claim 1, wherein the light-shielding film has an elastic modulus at −30° C. of 2500 MPa or more and 5100 MPa or less.
11. The optical element according to claim 1 , wherein the light-shielding film contains a dispersant having an amine value higher than an acid value.
12. A housing, and the optical element according to any one of claims 1 to 11 disposed inside the housing; An optical instrument having
13. A housing; an optical system including the optical element according to any one of claims 1 to 11 disposed inside the housing; and an imaging element that receives light incident through the optical system; An imaging device comprising:
14. A method for manufacturing an optical element, comprising the steps of: A step of bonding the first optical element and the second optical element with an adhesive that is a precursor of a third optical element; applying a light-shielding coating material to end faces of the first optical element, the second optical element, and the third optical element, and curing the coating material to form a light-shielding film; having The light-shielding film contains a resin and inorganic particles, the first optical element and / or the second optical element has a chamfer on a bonding surface side; At least one of the first optical element and / or the second optical element having the chamfered portion has a rounded portion on the bonding surface side, %。 Forming the light-shielding film, the light-shielding coating is cured so that the resin ratio of the light-shielding film is 87 vol % or more and 95 vol % or less.
15. A first optical element; and A second optical element; and a light-shielding film provided in contact with an end surface of the first optical element and a third optical element that bonds the second optical element, The light-shielding film contains a resin and inorganic particles, A light-shielding film having a resin ratio of 87 vol % or more and 95 vol % or less.
16. 16. The light-shielding film according to claim 15, wherein the maximum thickness of the light-shielding film in a portion in contact with the third optical element is 20 μm or more and 180 μm or less.
17. The light-shielding film according to claim 15, wherein the light-shielding film has an elastic modulus at −30° C. of 2500 MPa or more and 5100 MPa or less.
18. The light-shielding film according to claim 15 , comprising a dispersant having an amine value higher than an acid value.
19. A black light-shielding paint containing a resin, a colorant and inorganic particles, the light-shielding paint comprising a dispersant having an amine value higher than its acid value.
Citation Information
Patent Citations
Internal reflection-preventing black coating material for optical element
JP2013100456A
Cemented lens, optical system having the same, optical device, and method of fabricating cemented lens
JP2020024331A